“School should be a place where everyone feels comfortable and accepted”: An exploration of autistic adolescent girls’ lived experiences of emotional wellbeing in mainstream secondary schools - Roberts, Katie (2024)
Adolescence is a crucial stage for the emergence of mental health needs (Kessler et al., 2005), especially for autistic individuals who are likely to experience mental health challenges (Toseeb & Asbury, 2023). Most autistic pupils attend mainstream schools (National Autistic Society, 2021), placing these settings as key in shaping emotional wellbeing. Despite research recognising the unique needs of autistic girls and their increased likelihood of experiencing mislabelling or delayed diagnosis (Bargiela et al., 2016), existing school support models often neglect them (Kidd & Kaczmarek, 2010), leading to adverse emotional outcomes (Wild, 2019).